How Nest Site Characteristics Influence Breeding Success in Red-legged Cormorants Phalacrocorax gaimardi - Millones, Ana (2018)
For seabirds, nest site features are an important factor that determines reproductive success. During three breeding seasons (2010-2012), we visited two coastal cliff colonies of Red-legged Cormorants halacrocorax gaimardi in the Ría Deseado, Argentina, and studied how nest site characteristics influenced their breeding success. We measured six physical characteristics at 46 nest sites, and we counted the number of fledglings produced each year from each nest (breeding success). We also related nest site temperature and wind exposure with nest site orientation. Breeding success was higher at nest sites with a broad base (greater capacity for holding young) and at nests that were less exposed to winds greater than 25 knots (46.25 km/h), which were sites with a north orientation. The lowest breeding success was observed in nest sites that were exposed to the strongest winds (i.e., sites with a south orientation). Strong winds often blow eggs and chicks away from the nests and increase opportunistic predation by gulls Larus sp. No significant relationship was found between nest site orientation and nest site temperature. Breeding success decreased with the distance to the nearest nest, which agrees with the idea that higher density of reproductive individuals reduces effectiveness of predators. Nest cover, distance from the top of the cliff, and distance from the tide line had no effect on breeding success at this study scale. Our results suggested that nest site haracteristics that were related to protection against adverse weather conditions (e.g., strong winds) and avian predation, in combination with a suitable nest space, determined the breeding success of Red-legged Cormorants.